YouTube marketing communication demographic and usage variables influence on Gen Y's cognitive attitudes in South Africa and Romania. Issue 5 (20th May 2019) - Duffett, Rodney Graeme; Edu, Tudor; Negricea, Iliuta Costel
Abstract: The primary purposes of this study are to consider the influence of YouTube marketing communication (YMC) on awareness and knowledge among Generation (Gen) Y cohort respondents in South Africa (SA) and Romania (RO) and to establish if country, demographic, and usage (independent) variables have an effect on this cognitive attitudinal association. Multistage sampling was employed, and a survey was conducted among 400 respondents in SA and 400 respondents in RO. Structural equation modelling was used to investigate the hypothesized associations. The findings confirm that awareness had a favorable influence on knowledge for the total sample, SA and RO. The results also show that awareness displayed a significantly larger positive effect on knowledge among Romanian Gen Y in comparison with South African Gen Y. This study confirms that age (demographic variable) and access, usage length, log‐on frequency, log‐on duration, and advertisement viewership numbers (usage variables) have a significant effect on cognitive attitudinal responses due to YMC among Gen Y in SA and RO. Organizations should consider adapting YMC strategies to stimulate awareness, which will stimulate favorable knowledge attitudinal responses, as well as consider the aforementioned demographic and usage variables when targeting the infamously unpredictable Gen Y due to the positive cognitive attitudinal association in developing countries.